PENGETAHUAN PERAWAT MEMBERIKAN HIGH QUALITY CPR DAN KESIAPSIAGAAN DALAM MANAJEMEN BENCANA DI INSATALASI GAWAT DARURAT DI 4 RUMAH SAKIT DAERAH DI KAB. SEMARANG - Maksum; Dewi Siyamti; Purnomo (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Blockage of coronary arteries causes problems in the heart's electrical system, one of them is cardiac arrest occurs suddenly at any time and at anyone. The heart failure caused the supply of food to organs to decrease. As health workers, knowledge of High-QualityPR must be maintained by nurses in dealing with cardiac arrest, and as part of preparedness, nurses carry out their duties when disaster occurs. Objective: This research aims to determine nurses' knowledge of improving High-Quality CPR capabilities in practice settings and in disaster activities. Research method: this research used qualitative descriptive design using the Convenience Sampling Technique, namely sampling taken based on the wishes of the researcher based on convenience, adequacy, and cooperation. Research solution: nurses in carrying out their duties in health services and disaster preparedness must know High-Quality CPR and carry out activities to reduce disasters in patients who experience cardiac arrest problems. Conclusion: This research is expected to confirm in provision High Quality CPR services. Keywords: Cardiac Arrest, High-Quality CPR, Knowledge